Production of earthworm meal from Eisenia fetida (Savigny, 1826) as a tool for the management of manure - Valente, Beatriz Simões; Xavier, Eduardo Gonçalves (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
A trial was conducted to evaluate the production of earthworm meal from Eisenia fetida as a tool for the management of manure. A completely randomized design was used. The treatments were: 100% bovine manure (T1), 100% equine manure (T2) and 100% capybara manure (T3). Each treatment had five replications. A total of 50 adult and containing clitellum earthworms (Eisenia fetida) were inoculated in each experimental unity. The following analyses were performed: total nitrogen, crude protein, total phosphorus, potassium and total calcium. The results showed that the production of earthworm meal is an important tool for the management of different manure and it does not present any limitation of environmental nature. The substrates bovine manure, equine manure and capybara manure result in an earthworm meal containing a high content of crude protein. The proteic and mineral composition of earthworm meal are dependent on the quality and form of storage of the manure. The proper planning of the animal production system must contemplate an adequate place for the storage of the manure in order to maintain the quality of the substrate provided to the earthworms.